2020
DOI: 10.1111/1346-8138.15427
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of thyroid dysfunction in patients with erythrodermic psoriasis

Abstract: The association of psoriasis with thyroid dysfunction has been investigated. However, it remains unclear; some papers indicate it, and others do not. In this study, we evaluate the prevalence of thyroid dysfunction in patients with psoriasis vulgaris (PsV), psoriatic arthritis (PsA), generalized pustular psoriasis (GPP) and erythrodermic psoriasis (EP), and the association of thyroid dysfunction with inflammation. Data on 201 psoriatic patients visiting our hospital from January 2014 to November 2017 (159 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is well recognized that transient or subclinical biochemical or hormone dysfunctions may be detected using in vitro tests during acute illness, such as sick euthyroid syndrome. Zheng et al 12 reported that the highest likelihood of thyroid dysfunction (hypothyroidism) occurred in erythrodermic psoriasis compared with other forms of psoriasis, such as psoriasis vulgaris, psoriatic arthritis and generalized pustular psoriasis but it is unclear if these findings are transient. Co-occurrence of hyperthyroidism and erythroderma was reported in one case, although no autoimmune cause for the changes in thyroid function was identified, and the erythroderma resolved with normal thyroid function after a few weeks.…”
Section: Hormone Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that transient or subclinical biochemical or hormone dysfunctions may be detected using in vitro tests during acute illness, such as sick euthyroid syndrome. Zheng et al 12 reported that the highest likelihood of thyroid dysfunction (hypothyroidism) occurred in erythrodermic psoriasis compared with other forms of psoriasis, such as psoriasis vulgaris, psoriatic arthritis and generalized pustular psoriasis but it is unclear if these findings are transient. Co-occurrence of hyperthyroidism and erythroderma was reported in one case, although no autoimmune cause for the changes in thyroid function was identified, and the erythroderma resolved with normal thyroid function after a few weeks.…”
Section: Hormone Dysfunctionmentioning
confidence: 99%
“…It is well recognized that transient or subclinical biochemical or hormone dysfunctions may be detected using in vitro tests during acute illness, such as sick euthyroid syndrome. Zheng et al 12 . reported that the highest likelihood of thyroid dysfunction (hypothyroidism) occurred in erythrodermic psoriasis compared with other forms of psoriasis, such as psoriasis vulgaris, psoriatic arthritis and generalized pustular psoriasis but it is unclear if these findings are transient.…”
Section: Potential Mechanisms Impacting On Energy Homeostasis In Erythrodermamentioning
confidence: 99%
“…12 Furthermore, according to a recent study from China, a higher prevalence of thyroid dysfunction was found in EP patients. 13 Several human leukocyte antigens (HLA), such as HLA-Cw6 and HLA-DR7 have been linked with psoriasis vulgaris, 14,15 and the same genetic constitution was also related to guttate psoriasis. 16 In Chinese patients with erythrodermic psoriasis, HLA-C*01:02 was reported to be the most frequent HLA-C allele (34.4%) compared to plaque psoriasis (21.9%) and healthy controls (21.2%).…”
mentioning
confidence: 99%